An advanced pseudo excitation method and application in analyzing stochastic wind-induced response of slender bridge tower. Issue 9 (July 2019) - Zhu, Siyu; Xiang, Tianyu; Li, Yongle
Based on the theory of pseudo excitation method, a so-called stochastic pseudo excitation method is proposed to acquire the sampling results of stochastic dynamic response of uncertain bridge structure directly, which cannot be achieved by the classical pseudo excitation method. In order to reduce the computational cost of the dynamic finite element analysis of the samples to gain the probability density function of structural responses, the response surface method was adopted to handle the sampling results. The stochastic pseudo excitation method combing response surface method is verified by comparing with Monte Carlo method in good agreement. As an example, the stochastic response of a super-high slender bridge tower subjected to the Davenport fluctuating wind excitations is evaluated taking into account the uncertainties of material properties and wind speed. Numerical results show that the effect of uncertainties of structure or excitations plays a constant role in the stochastic response at the different levels of external excitations.